Marcos de referência e topónimos da cidade medieval portuguesa: o exemplo de Coimbra nos séculos XIV e XV - Campos, Maria Amélia Álvaro de (2013)
With this article, we pretend to conduct an analysis about the city toponymy of the Portuguese Middle Ages, from the more detailed study of the reality of Coimbra, in the fourteenth and fifteenth centuries. Based on a body of documents consisting on documents written by ecclesiastical, district and royal institutions, chronologically marked out between the fourteenth century and the beginning of the sixteenth century, this work seeks to identify the main topographic landmarks, either natural or built, that stood out in the urban landscape. In the same way, wishes to emphasize the way the medieval toponymy gives us echoes from the population that gave life to the city in the centuries that we now study, but also the people who, protagonists of previous occupations, left until late a distinctive stamp in the urbanism of Coimbra. Finally, this study aims a better comprehension of the relationship that was established between the city inhabitant and the urban space. For a better articulation of these issues, this article is divided in four themes highlighted by the toponymy in review: buildings and urban constructions; landscapes and natural features; craft and commercial activities and other professions; religious and foreign minorities.